Financial literacy levels among Saudi citizens across budgeting, saving, investment, debt, and insurance dimensions - Naseem M. Al Rahahleh (Journal of Risk and Financial Management, 2022)
This paper provides a comprehensive account of financial literacy among Saudi citizens. Responses to items about key aspects of financial literacy-i.e., budgeting, debt, saving, investment, and insurance-were elicited from a large sample of Saudi citizens through an online survey. The data from 887 completed surveys were subjected to a descriptive analysis, a T-test, and ANOVA. A high level of financial literacy was found among the respondents in relation to budgeting, debt, and saving, but only a moderate level in relation to investment and insurance. The study findings indicate that current efforts on the part of government agencies, schools, universities, and financial institutions focused on budgeting, debt, and saving should continue and that more attention should be paid to educating Saudi citizens in relation to investment and insurance.
Keywords: 650; financial literacy; investment; debt; budgeting; financial decisions; insurance; Saudi citizens; saving